Correlation between the seric levels of dehidroepiandrosterone sulphate with the skeletal maturation stages: final paper - Giraldo, Mónica; Barbosa, Diana; Zapata, Óscar; Jaramillo, Hilda Norha (Revista Facultad de Odontología Universidad de Antioquia, 2009)
In order to detect an indicator of the onset of pubertal spurt, the DHEAS serie levels were correlated with age, weight, height, skeletal maturity stage (Hägg and Taranger) and sexual maturity (Tanner and, Prader). 33 patients; 18 males and 15 females, between 8 and 12 years old were studied. Healthy children in Tanner I sexual maturity stage was the research criteria for inclusion. The data were taken every six months during three years (2000-2002). The behavior of the anthropometric variables of the general population was published in a previous paper. In the group of males, we did not found any significant correlation between the seric levels of DHEAS with the studied variables, except for the weight at the beginning of the study. In the female group, a correlation was found with the ulnar sesamoid although not in the long term, and with the weight in the middle of the study. However, none of these associations and correlations confirmed our initial hypothesis because the correlations found were considerate such as isolated facts.